2021
DOI: 10.3390/children8080667
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular MDCT Findings of Pulmonary Vein Stenosis in Children with Cardiac Septal Defect

Abstract: To retrospectively investigate the extravascular thoracic MDCT angiography findings of pulmonary vein stenosis (PVS) in children with a cardiac septal defect. Materials and Methods: Pediatric patients (age ≤ 18 years) with cardiac septal defect and PVS, confirmed by echocardiogram and/or conventional angiography, who underwent thoracic MDCT angiography studies from April 2009 to April 2021 were included. Two pediatric radiologists independently evaluated thoracic MDCT angiography studies for the presence of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 26 publications
(54 reference statements)
2
4
0
Order By: Relevance
“…The findings of our study correlate well with the findings from previously published studies in pediatric patients with primary and secondary PVS focusing on extrathoracic MDCT findings [16][17][18]. These studies also identified the presence of three main extravascular pleuropulmonary abnormalities on thoracic MDCT in pediatric patients with PVS: GGO, septal thickening, and pleural thickening.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The findings of our study correlate well with the findings from previously published studies in pediatric patients with primary and secondary PVS focusing on extrathoracic MDCT findings [16][17][18]. These studies also identified the presence of three main extravascular pleuropulmonary abnormalities on thoracic MDCT in pediatric patients with PVS: GGO, septal thickening, and pleural thickening.…”
Section: Discussionsupporting
confidence: 90%
“…Presented clinical signs and symptoms in these 49 pediatric patients included: failure to thrive (n = 8; 16.3%), pulmonary hypertension (n = 7; 14.3%), shortness of breath (n = 5; 10.2%), hypoxemia (n = 5; 10.2%), fever (n = 3; 6.1%), and bradycardia (n = 2; 4.1%). Extrapulmonary MDCT findings for a subset of these patients were previously reported [16][17][18].…”
Section: Patient Population Characterizationmentioning
confidence: 76%
See 3 more Smart Citations